Extracellular exosome signature links hypertension and Alzheimer’s disease - Joakim A. Bastrup; Jonas Folke; Sanne S. Kaalund; Michel Rasmussen; Susana Aznar; Thomas Jepps (GeroScience, 2026)
Untreated hypertension is a risk factor for late-onset Alzheimer’s disease (AD); however, this association is not well understood. The aim of this study was to reveal protein signatures that bridge the pathophysiological changes in hypertension to AD. Using untargeted proteomics, we analyzed brain samples from aged (30- and 40-week-old) spontaneously hypertensive rats (SHRs, n = 12), and age-matched normotensive Wistar Kyoto (WKY, n = 8) controls, and human AD patients (Braak stages 4–6) ( n = 30), cerebral amyloid angiopathy (CAA) ( n = 5), non-demented controls (Braak stages 0–3) ( n = 37). Differential expression and pathway analyses in SHRs highlighted the ‘extracellular exosome’ pathway. This pathway also showed significant associations to differentially expressed proteins in AD and CAA patients. Comparison between species identified 24 proteins in SHRs and AD, whose trajectory pattern over the progression of hypertension, aligned with those observed during AD Braak stage progression, compared to respective controls. The proteins were similarly associated with extracellular exosomes. Immunostaining and spatial proteomics support vesicle accumulation and dysregulated exosome protein signatures in the cerebrovasculature of both SHR and AD brains. Additionally, the extracellular exosome pathway-association was not identified in a traditional model of familial AD (5xFAD). Our findings demonstrate cross-species translatability between AD and the SHR and provide novel mechanistic insights into a shared dysregulation of cerebral artery-associated exosomes. Graphical Abstract

Database development and LIBS calibration for the LIBS-Raman Sensor for planetary exploration - E.R. Sawyers; G. Lopez-Reyes; A. Barlow; M. Veneranda; E.A. Lymer; E.A. Cloutis; J. Manrique; B. Barrios; S. Julve; J. Freemantle; M. Aznar; M.G. Daly; et al. (Icarus, 2025)

Increased rupture of cypress pollen type due to atmospheric water in central and southeastern Spain - F. Aznar; L. Negral; S. Moreno-Grau; I. Costa; B. Lara; J. Romero-Morte; J. Rojo; R.M. Rodríguez-Arias; F. Fernández-González; R. Pérez-Badia; J.M. Moreno (Science of The Total Environment, 2024)

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

Initial evaluation of USP apparatus 4 for measuring dissolution profile of man-made vitreous fibers - J.W. Hoffman; D.V. Okhrimenko; E. Chaudan; Q. Herault; N. Drnovsek; E. Pezennec; A. Aznar; N. Mascaraque; S. Haddouchi; M. Lecluse; A.A. Badissi; J. de Cruz; et al. (Toxicology Letters, 2023)

Raman-IR spectroscopic, and XRD analysis of selected samples from Fogo Island, Cabo Verde: Implications for ancient Martian volcanology - M. Aznar; A. Sanz-Arranz; S. Shkolyar; E.R. Sawyers; M. Konstantinidis; G. Lopez-Reyes; M. Veneranda; E.A. Lymer; J.R. Freemantle; M.G. Daly; E.A. Cloutis; F. Rull-Perez; et al. (Advances in Space Research, 2023)

Epibiotic Fauna on Cetaceans Worldwide: A Systematic Review of Records and Indicator Potential - S. Ten; J. A. Raga; F. J. Aznar (Frontiers in Marine Science, 2022)
Each individual cetacean is an ecosystem itself, potentially harboring a great variety of animals that travel with it. Despite being often despised or overlooked, many of these epizoites have been proven to be suitable bio-indicators of their cetacean hosts, informing on health status, social interactions, migration patterns, population structure or phylogeography. Moreover, epizoites are advantageous over internal parasites in that many of them can be detected by direct observation (e.g., boat surveys), thus no capture or dissection of cetaceans are necessary. Previous reviews of epizoites of cetaceans have focused on specific geographical areas, cetacean species or epibiotic taxa, but fall short to include the increasing number of records and scientific findings about these animals. Here we present an updated review of all records of associations between cetaceans and their epibiotic fauna (i.e., commensals, ecto- or mesoparasites, and mutualists). We gathered nearly 500 publications and found a total of 58 facultative or obligate epibiotic taxa from 11 orders of arthropods, vertebrates, cnidarians, and a nematode that are associated to the external surface of 66 cetacean species around the globe. We also provide information on the use as an indicator species in the literature, if any, and about other relevant traits, such as geographic range, host specificity, genetic data, and life-cycle. We encourage researchers, not only to provide quantitative data (i.e., prevalence, abundance) on the epizoites they find on cetaceans, but also to inform on their absence. The inferences drawn from epizoites can greatly benefit conservation plans of both cetaceans and their epizoites.

Cellular and Molecular Changes in Hippocampal Glutamate Signaling and Alterations in Learning, Attention, and Impulsivity Following Prenatal Nicotine Exposure - Filip S. Polli; Theis H. Ipsen; Maitane Caballero-Puntiverio; Tina Becher Østerbøg; Susana Aznar; Jesper T. Andreasen; Kristi A. Kohlmeier (Molecular Neurobiology, 2020)

Target of rapamycin signaling is tightly and differently regulated in the plant response under distinct abiotic stresses - Cintia M. Pereyra; Néstor R. Aznar; Marianela S. Rodriguez; Graciela L. Salerno; Giselle M. A. Martínez-Noël (Planta, 2020)

Tryptophan depletion affects compulsive behaviour in rats: strain dependent effects and associated neuromechanisms - A. Merchán; S. V. Navarro; A. B. Klein; S. Aznar; L. Campa; C. Suñol; M. Moreno; P. Flores (Psychopharmacology, 2017)

Trunk spines in cystacanths and adults of Corynosoma spp. (Acanthocephala): Corynosoma cetaceum as an exceptional case of phenotypic variability - Francisco J. Aznar; Enrique A. Crespo; Juan A. Raga; Jesús S. Hernández-Orts (Zoomorphology, 2016)

An improved taxonomic sampling is a necessary but not sufficient condition for resolving inter-families relationships in Caridean decapods - L. Aznar-Cormano; J. Brisset; T.-Y. Chan; L. Corbari; N. Puillandre; J. Utge; M. Zbinden; D. Zuccon; S. Samadi (Genetica, 2015)

Geological risk assessment of Amtoudi Agadir in southern Morocco: a key case for sustainable cultural heritage - P. Robles-Marín; F. Guerrera; M. Martín-Martín; G. Raffaelli; F. J. Alcalá; J. Tejera de León; T. E. Cherkaoui; L. Asebriy; I. E. El Amrani; S. Moliner-Aznar (Natural Hazards, 2015)

Interpolation of monthly mean temperatures using cokriging in spherical coordinates - J.‐C. Aznar; E. Gloaguen; D. Tapsoba; S. Hachem; D. Caya; Y Bégin (International Journal of Climatology, 2013)
Paleoclimate reconstructions are generally validated on recent periods. To obtain a set of instrumental records at the regional scale, a time series of monthly mean temperatures in Northeastern Canada were interpolated for the 1961–2000 period. Records were provided by 202 meteorological stations. Temperatures derived from a Canadian regional climate model (Climate Model CRCM 4.2.3 from the AMNO domain produced at ∼50 km resolution) were added as secondary information to take into account local heterogeneity and temporal dependencies. Geostatistical interpolation of the measured temperature was calculated using CRCM modelled data as a covariable and then compared to an ordinary kriging performed on a time series of mean temperature anomalies. Spherical distances between locations were calculated taking into account the curvature of the Earth with monthly semivariances being modelled using Cauchy variograms. Mean absolute error values (1.5 ± 1.2 °C) were calculated for the whole period using cross‐validation procedures. Errors were found to have the same order of magnitude in the central part of the study area where few recorded temperatures were available. Monthly mean temperature grids are publicly available through the Institut National de la Recherche Scientifique ( http://url.in.rs/3P ). Copyright © 2012 Royal Meteorological Society

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)